2022
DOI: 10.1039/d1ra08809b
|View full text |Cite
|
Sign up to set email alerts
|

Insight into carbon quantum dot–vesicles interactions: role of functional groups

Abstract: An interaction study at the nano–bio interface involving phosphatidylcholine vesicles (as a model cell membrane) and four different carbon dots bearing different functional groups (–COOH, –NH2, –OH, and BSA-coated).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The reason behind this boosted emission should be sought in more homogenous dispersity of the fluorescent NPCQDs inside the PVA matrix, minimizing the reabsorption effect 27 . As confirmed by XRD results, as a result of the formation of the NP-PVA composite, a significant enhancement was observed in the crystallinity, due to higher numbers of hydrogen bondings between hydroxyl groups of PVA (-OH) and carboxyl (–COOH) groups on the edges of the NPCQDs 28 , leading to rearrangement and reordering of NPCQDs inside PVA chains and thus boosting the crystallinity, and the homogeneity in the dispersity of the NPCQDs. The PVA used in this study, with above 98% of hydrolysis degree, had a large number of hydroxyl groups, making it extensively capable of hydrogen bonding.…”
Section: Resultsmentioning
confidence: 65%
“…The reason behind this boosted emission should be sought in more homogenous dispersity of the fluorescent NPCQDs inside the PVA matrix, minimizing the reabsorption effect 27 . As confirmed by XRD results, as a result of the formation of the NP-PVA composite, a significant enhancement was observed in the crystallinity, due to higher numbers of hydrogen bondings between hydroxyl groups of PVA (-OH) and carboxyl (–COOH) groups on the edges of the NPCQDs 28 , leading to rearrangement and reordering of NPCQDs inside PVA chains and thus boosting the crystallinity, and the homogeneity in the dispersity of the NPCQDs. The PVA used in this study, with above 98% of hydrolysis degree, had a large number of hydroxyl groups, making it extensively capable of hydrogen bonding.…”
Section: Resultsmentioning
confidence: 65%
“…Considering that FA CNDs are rich in polar groups, we assign interactions between them and the hydrophilic part of DLPC to electrostatic forces as well as hydrogen bonding. In the presence of negatively charged FA CNDs, the tilt angle of the DLPC headgroup can be altered to facilitate the electrostatic attraction forces between the dopants and the quaternary ammonium cation. , Furthermore, the oxygen-containing phosphate groups with lone-pair electrons appear as acceptors (bases) in the formation of hydrogen bonds with the protic moieties of FA CNDs (e.g., amino or hydroxyl groups) …”
Section: Resultsmentioning
confidence: 99%
“…99,100 Furthermore, the oxygen-containing phosphate groups with lone-pair electrons appear as acceptors (bases) in the formation of hydrogen bonds with the protic moieties of FA CNDs (e.g., amino or hydroxyl groups). 101 The fluorescence microscopic studies indicated that FA CNDs are present within the whole volume of MFs (with a high content of CNDs in the water core and lower contribution in the multilayered walls). Combining these results and potential interactions of hydrophilic negatively charged dopants with the phosphatidylcholine headgroups, we consider that FA CNDs are located in the aqueous phase of MFs (i.e., in the water core as well as aqueous layers between lipid bilayers) and can be adsorbed onto lipid bilayer−water interfaces.…”
Section: One-photon Excited Fluorescence Imaging Of Mfsmentioning
confidence: 99%
“…Boruah et al used phosphatidylcholine vesicles as a cell membrane model to study the interaction between CQDs carrying four different functional groups including the carboxyl group (-COOH), the amino group (-NH 2 ), the hydroxyl group (-OH) and a BSA protein envelope. 230 Verification via PL, vesicle surface charge, FTIR and other characterization methods showed that the CQDs-NH 2 had a strong binding ability with vesicles, while the other three CQDs showed no obvious interaction. It may be that the lone pair of electrons on the phosphate oxygen atom can form hydrogen bonds with the two H atoms on the free -NH 2 , making CQDs-NH 2 firmly adsorbed on the vesicle.…”
Section: Carbon Quantum Dotsmentioning
confidence: 97%